Development of a method for capturing human motion using a RGB-D camera - Da Motta, Everton Simoes [UNESP] (2017)
Human motion capture systems are being increasingly studied in the area of computer vision and also by major entertainment industries. These systems are able to track the position and orientation of joints of the body and its trajectory in space over a period of time. They are used in various applications such as digital games, animation of virtual characters for film and television, gesture recognition, medical rehabilitation, etc. The emergence of new low-cost and good resolution devices that provide depth information has prompted new research. However, systems that are based only on depth information (usually realtime systems) do not present a high accuracy in movement tracking. Considering this context, this thesis project presents the development of a method for capturing human movements using only one RGB-D sensor, combining captured texture from the image and depth information in order to obtain a higher accuracy of the inferred motion, which are associated with a virtual skeleton. This method is not intended for real-time applications (like video games), but those that require greater accuracy, such as the animation of virtual characters, for film, and medical rehabilitation.